Public Sector Accounting and Financial Management Systems in the Context of Socioeconomic Development: An Empirical Study of the Volta River Authority in Ghana - Abdul-Rahaman, Abu Shiraz; Lawrence, Stewart; Gallhofer, Sonja; Haslam, Jim (Accounting Department,, 1998)
The role of accounting in socioeconomic development has been signiï¬cantly documented in the international accounting literature. However, a majority of these prior studies represent accounting as a technical neutral craft which plays (or can play) an enabling role in national socioeconomic development. This study contends that in some situations conventional accounting with its emphasis on the entity concept can play a constraining role in national socioeconomic development efforts. This is illustrated by an empirical study of the Volta River Authority. A major public sector organisation in Ghana. The paper is informed by the Brundtland Commission's notion of sustainable development.